2012
DOI: 10.1080/1369118x.2012.665467
|View full text |Cite
|
Sign up to set email alerts
|

(Re-)Discovering the Audience

Abstract: RE-)DISCOVERING THE AUDIENCEThe relationship between journalism and audience in networked digital media Current technological, organizational and institutional changes fundamentally alter the relationship between journalism and its audience -with consequences not only for journalistic practice, but also for theoretical and methodological issues of media research. After briefly recounting three perspectives on the audience, the paper outlines key aspects of the sociological theory of inclusion and explicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(66 citation statements)
references
References 55 publications
2
52
0
1
Order By: Relevance
“…It complements previous audience studies in which patterns of moderate use of participatory features were found (Bergström, 2008;Chung and Nah, 2009;Hujanen and Pietikäinen, 2004;Larsson, 2011) by suggesting an additional explanation for not, or no longer, participating: the viability of participatory projects could also be diminished by a need and wish for, but a factual lack of, reciprocity. This article, thus, further emphasizes the value of the notion of reciprocity (Lewis et al, 2013;Loosen and Schmidt, 2012) for the study and practice of participatory journalism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It complements previous audience studies in which patterns of moderate use of participatory features were found (Bergström, 2008;Chung and Nah, 2009;Hujanen and Pietikäinen, 2004;Larsson, 2011) by suggesting an additional explanation for not, or no longer, participating: the viability of participatory projects could also be diminished by a need and wish for, but a factual lack of, reciprocity. This article, thus, further emphasizes the value of the notion of reciprocity (Lewis et al, 2013;Loosen and Schmidt, 2012) for the study and practice of participatory journalism.…”
Section: Discussionmentioning
confidence: 99%
“…Note that journalism as a social system only functions well if the actors that are part of the system have 'reciprocal expectations' of each other's 'roles' (Loosen and Schmidt, 2012). Traditional journalism was such a functioning social system, because expectations of journalists as gatekeepers and audience as receivers were 'fairly stable and reciprocal' (Loosen and Schmidt, 2012: 870).…”
Section: Expecting Reciprocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different concepts have been suggested to capture this new reality: "recursive publics" (Kelty, 2005), "networked publics" (boyd, 2011), or "ad hoc publics" (Bruns & Burgess, 2015). Loosen and Schmidt (2012) suggest the apparition of new forms of public spheres that are provisionary, formed, for example, around a Facebook page created spontaneously about a specific issue. Blondeau and Allard (2010) suggest that, through their reflexive engagement on social media, users constitute themselves as public of texts, and by the same token contribute to define and expand these texts.…”
Section: Users As Publicsmentioning
confidence: 99%
“…Feedback is instant" (quoted in Este et al 2008, 17). Research suggests that news editors are increasingly using this feedback to guide their news production -for example, if metrics show that a particular story is popular, placing it prominently on the website homepage, and commissioning stories on a similar topic in the future (Anderson 2011a(Anderson , 2011bBoczkowski, 2004;Bright and Nichols 2014;Dick 2011;Loosen and Schmidt 2012;MacGregor 2007;Peters 2010). …”
mentioning
confidence: 99%